Manželské etudy – 3. Ivana a Václav . Marriage Stories – 3. Ivana and Václav - Třeštíková, Helena (Beckov, Anna, 1987)
Duration: 00:36:00 In 1987, Helena Treštíková directed a series for Czech television called "Marriage Stories" about young married couples. "Ivana and Vaclav" is one of the episodes of the series, a portrait shot from 1980 to 1987 of two people in their early twenties embarking on married life and parenthood. As they try to continue their studies while raising a child in a tiny apartment, Ivana and Vaclav keep their faith in the future despite their tough living conditions.